2000
DOI: 10.1164/ajrccm.161.1.ats11-99
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Methacholine and Exercise Challenge Testing—1999

Abstract: This statement provides practical guidelines and suggestions for methacholine and exercise challenging testing. Specifically, it reviews indications for these challenges, details factors that influence the results, presents brief step-by-step protocols, outlines safety measures, describes proper patient preparation and procedures, provides an algorithm for calculating results, and offers guidelines for clinical interpretation of results. The details are important because methacholine and exercise challenge tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
457
0
19

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,110 publications
(481 citation statements)
references
References 184 publications
(220 reference statements)
5
457
0
19
Order By: Relevance
“…Subjects were characterized during a baseline visit assessing impulse oscillometry (IOS), spirometry, body plethysmography and a conventional nebulized AMP bronchoprovocation test. [913] Subjects with a positive AMP response (PC 20  ≤ 320 mg ml –1 ) on this baseline visit were included.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were characterized during a baseline visit assessing impulse oscillometry (IOS), spirometry, body plethysmography and a conventional nebulized AMP bronchoprovocation test. [913] Subjects with a positive AMP response (PC 20  ≤ 320 mg ml –1 ) on this baseline visit were included.…”
Section: Methodsmentioning
confidence: 99%
“…Tests were carried out on a separate day from the Mannitol test. Using an inhalation-triggered dosimeter (Spira Respiratory Care Centre Ltd, Hämeenlinna, Finland), subjects inhaled nebulized isotonic saline for baseline measurement followed by 1–5 incremental doses of nebulized methacholine, as described by Crapo [13]. Two minutes after each inhaled dose, a spirometry measurement was carried out.…”
Section: Assessmentmentioning
confidence: 99%
“…Of the 29 included patients, 55% were men, 2 out of 3 were treated with ICS, mean FEV 1 was 84 [13] %pred and mean ACQ score was 1.7 (0.6) (Table 1). A total of 28 (97%) had a mannitol test performed, and of these, 21 (75%) had a positive test.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Challenges by the inhalation of methacholine or histamine and by exercise have been widely used in the evaluation of asthma with the overall impression that the worse the hyperreactivity the worse the asthma [58, 59, 60]. However, even in the most recent recommendations for the performance of bronchial provocation tests [61], arbitrary criteria have been used to define an abnormal response and this can easily lead to confusion. We have shown that valid normal ranges can be defined statistically and should be used when determining whether a subject with respiratory symptoms is abnormal in terms of bronchial reactivity [62].…”
Section: Measurement Of Bronchial Reactivitymentioning
confidence: 99%